Semantic Analysis of Verbal Collocations with Lexical Functions - Gelbukh, Alexander; Kolesnikova, Olga.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book is written for both linguists and computer scientists working in the field of artificial intelligence as well as to anyone interested in intelligent text processing. Lexical function is a concept that formalizes semantic and syntactic relations between lexical units. Collocational relation is a type of institutionalized lexical relations which holds between the base and its partner in a collocation. Knowledge of collocation is important for natural language processing because collocation comprises the restrictions on how words can be used together. The book shows how collocations can be annotated with lexical functions in a computer readable dictionary - allowing their precise semantic analysis in texts and their effective use in natural language applications including parsers, high quality machine translation, periphrasis system and computer-aided learning of lexica. The books shows how to extract collocations from corpora and annotate them with lexical functions automatically. To train algorithms, the authors created a dictionary of lexical functions containing more than 900 Spanish disambiguated and annotated examples which is a part of this book. The obtained results show that machine learning is feasible to achieve the task of automatic detection of lexical functions.
Introduction -- Lexical Functions and their Applications -- Identification of Lexical Functions -- Meaning Representation -- Analysis of Verbal Collocations with Lexical Functions -- Linguistic Interpretation -- Dictionary of Spanish Verbal Lexical Functions.
Keywords: Engineering; Artificial intelligence; Translators (Computer programs).; Computational linguistics; Semantics; Engineering; Computational Intelligence; Computational Linguistics; Semantics; Artificial Intelligence (incl. Robotics).; Language Translation and Linguistics